STRATEGI KEPEMIMPINAN TERHADAP MOTIVASI KERJA PEGAWAI LEMBAGA PENYIARAN PUBLIK RADIO REPUBLIK INDONESIA BUKITTINGGI - Meilina, Susiyanti; Permanasari, Annisa (Ensiklopedia of Journal, 2021)
The objectives of this study are: 1) To determine the leadership strategy in increasing employee motivation at LPP RRI Bukittinggi; 2) To find out solutions in dealing with obstacles faced by leaders to increase employee motivation at LPP RRI Bukittinggi. This research was conducted using a qualitative approach. The qualitative descriptive approach according to Mukhtar (2013) is a research that is intended to reveal an empirical fact in an objective scientific manner based on the scientific logic that is occupied. Informants are people who are used to provide information about the situation and condition of the research setting. So he continues to have a lot of experience in the research setting. As a team member with kindness, volunteering can provide views on values, attitudes and culture, which are the background for local research (Moleong; 2012: 90). The types of data are primary data and secondary data. Data collection techniques were collected through interviews, observations, and library research. The analysis technique used is qualitative analysis. The results of this study indicate that: the leadership strategy applied by the Head of RRI Bukittinggi Station is transformational leadership, proven to fulfill all the dimensions possessed by transformational leadership, namely charismatic, inspirational, individual consideration and intellectual stimulation. Broadly speaking, the leadership of the Head of LPP RRI Bukittinggi Station is modern leadership that humanizes humans. Leaders view humans or subordinates in their company not as objects, but as individuals who have the same character, traits, weaknesses, and strengths as leaders. The transactional leadership dimension does not apply to his leadership style. He does not give rewards or exceptions and special rules to his subordinates. The forms of motivation given by the head of the LPP RRI Bukittinggi station are establishing good personal relationships with employees (subordinates) in the form of giving rewards to employees who excel, gathering and evaluating together with employees, giving freedom to be creative and developing themselves, giving freedom of opinion (participation). employee).